2011
DOI: 10.1038/emboj.2011.222
|View full text |Cite
|
Sign up to set email alerts
|

The cohesin subunit RAD21L functions in meiotic synapsis and exhibits sexual dimorphism in fertility

Abstract: The cohesin complex is a ring-shaped proteinaceous structure that entraps the two sister chromatids after replication until the onset of anaphase when the ring is opened by proteolytic cleavage of its a-kleisin subunit (RAD21 at mitosis and REC8 at meiosis) by separase. RAD21L is a recently identified a-kleisin that is present from fish to mammals and biochemically interacts with the cohesin subunits SMC1, SMC3 and STAG3. RAD21L localizes along the axial elements of the synaptonemal complex of mouse meiocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
200
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(223 citation statements)
references
References 64 publications
17
200
1
4
Order By: Relevance
“…Structural changes caused by H2AX phosphorylation might contribute to making easier the physical proximity of AEs to promote the establishment of centromere pairing and/or to provide a docking site to facilitate the recruitment of the SC components, as it occurs with cohesins, which are recruited to meiotic DSB sites in a gH2AX-dependent manner (Ü nal et al 2004), thus contributing to the assembly of AEs during leptotene (Eijpe et al 2000, Pelttari et al 2001, James et al 2002. Actually, a role in synapsis completion in male spermatocytes has been found for the cohesin subunit RAD21L, a recently identified kleisin that localises along AEs and LEs and, as H2AX, exhibits sexual dimorphism in fertility (Celeste et al 2002, Herrán et al 2011. From this point of view, the arrays of gH2AX foci, which are shown for the first time in this study and which seem to embrace two or more AEs together in Spo11 K/K asynaptic zygotene spermatocytes, might play a role in promoting non-homologous synapsis.…”
Section: Discussionmentioning
confidence: 99%
“…Structural changes caused by H2AX phosphorylation might contribute to making easier the physical proximity of AEs to promote the establishment of centromere pairing and/or to provide a docking site to facilitate the recruitment of the SC components, as it occurs with cohesins, which are recruited to meiotic DSB sites in a gH2AX-dependent manner (Ü nal et al 2004), thus contributing to the assembly of AEs during leptotene (Eijpe et al 2000, Pelttari et al 2001, James et al 2002. Actually, a role in synapsis completion in male spermatocytes has been found for the cohesin subunit RAD21L, a recently identified kleisin that localises along AEs and LEs and, as H2AX, exhibits sexual dimorphism in fertility (Celeste et al 2002, Herrán et al 2011. From this point of view, the arrays of gH2AX foci, which are shown for the first time in this study and which seem to embrace two or more AEs together in Spo11 K/K asynaptic zygotene spermatocytes, might play a role in promoting non-homologous synapsis.…”
Section: Discussionmentioning
confidence: 99%
“…Although failure at synapsis leads to meiotic arrest and sterility in the corresponding mutant male mice, we found no effect on overall female fertility. Similarly, others have found mutations in meiotic genes, such as Pms2 and Rad21L, to cause male sterility whereas females remain fertile (Baker et al, 1995;Herrán et al, 2011). In addition, the loss of pachytene, but not pre-pachytene, piRNAs causes male sterility in mice with no effect on retrotransposon expression (Zheng and Wang, 2010), suggesting that these two events are differentially regulated.…”
Section: Miyagawamentioning
confidence: 99%
“…For cryosections, embryonic day (E)17.5, P5 and adult gonads were fixed (5% paraformaldehyde) and processed (Yamaguchi et al, 2006) then 10-μm sections were incubated with relevant primary antibodies [MVH (1:500, Abcam13840), MILI (1:50, Abcam36764), TDRD9 (Shoji et al, 2009), GASZ (Ma et al, 2009) (Herrán et al, 2011).…”
Section: Indirect Immunofluorescence Assays (Ifa) and Histologymentioning
confidence: 99%
“…Meiotic cohesin is crucial not only for sister chromatid cohesion but also to act as a structural basis for axial element (AE) formation and synaptonemal complex (SC) assembly during prophase I (Klein et al 1999;Zickler and Kleckner 1999;Prieto et al 2001;Page and Hawley 2004;Novak et al 2008;Llano et al 2012). Recent studies in mice have identified a novel meiosis-specific a-kleisin subunit of cohesin, RAD21L (Herran et al 2011;Ishiguro et al 2011;Lee and Hirano 2011), in addition to the previously identified REC8 (Bannister et al 2004;Xu et al 2005). RAD21L and REC8 form distinct cohesin complexes and distribute uniquely along each chromosome but identically between homologs during early meiotic prophase I, whereas the mitotic a-kleisin subunit RAD21 appears only transiently at the later pachytene stage in meiosis (Ishiguro et al 2011;Lee and Hirano 2011).…”
mentioning
confidence: 99%